Radiofrequency Ablation Resulting in Left Lobe Hypertrophy and Improved Resectability - R.T. Jones; J.J. French; J. Scott; D.M. Manas; R.M. Charnley (Case Reports in Gastroenterology, 2011)
Surgical resection for colorectal liver metastases may only be considered when an adequate functional residual volume can be preserved. Selective portal venous embolisation may be used to increase this volume, whilst chemotherapy and radiofrequency ablation (RFA) can be used to treat inoperable lesions. A 73-year-old man with liver metastasis proceeded to surgery, with the intention to perform a right hemi-hepatectomy. Unexpectedly at laparotomy, despite adequate pre-operative imaging, both the right and middle hepatic veins were involved. At that time extended right hemi-hepatectomy was contraindicated by insufficient residual volume and RFA was performed. Follow-up imaging revealed atrophy of the lesion. Significantly, there was also left lateral lobe hypertrophy sufficient to permit resection, which was performed without complication. Thrombosis of intra-hepatic portal veins is a recognised complication of RFA but here it appears to have been beneficial. The case highlights the need for regular review of unresectable hepatic disease by a liver surgeon and could suggest new modalities of portal embolisation.